Multimodal Sensing with a Three-Dimensional Piezoresistive Structure - Won, Sang Min; Wang, Heling; Kim, Bong Hoon; Lee, Kunhyuck; Jang, Hokyung; Kwon, Kyeongha; Han, Mengdi; Crawford, Kaitlyn E.; Li, Haibo; Lee, Yechan; Yuan, Xuebo; Kim, Sung Bong; et al. (ACS Nano, 2019)
Sensors that reproduce the complex characteristics of cutaneous receptors in the skin have important potential in the context of artificial systems for controlled interactions with the physical environment. Multimodal responses with high sensitivity and wide dynamic range are essential for many such applications. This report introduces a simple, three-dimensional type of microelectromechanical sensor that incorporates monocrystalline silicon nanomembranes as piezoresistive elements in a configuration that enables separate, simultaneous measurements of multiple mechanical stimuli, such as normal force, shear force, and bending, along with temperature. The technology provides high sensitivity measurements with millisecond response times, as supported by quantitative simulations. The fabrication and assembly processes allow scalable production of interconnected arrays of such devices with capabilities in spatiotemporal mapping. Integration with wireless data recording and transmission electronics allows operation with standard consumer devices.
Keywords: Electro-mechanical sensors; Electronic skin; High sensitivity measurement; Microelectromechanical sensors; Piezoresistive structures; Silicon nanomembrane; Simultaneous measurement; Tactile sensors; Biosensing Techniques; Electronics; Mechanical Phenomena; Physical Phenomena; Skin; Temperature; Touch; electromechanical sensor; electronic skin; silicon nanomembrane; tactile sensor; three-dimensional